TRANSFORMASI PERILAKU KOMUNIKASI PENGGUNA GAME ONLINE MOBILE LEGEND: BANG BANG (STUDI KASUS PADA PELAJAR SMA NEGERI 1 RANTAU SELATAN) - Indry Ayu Desvira; Nursapia Harahap; Indira Fatra Deni (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research is entitled "Transformation of Communication Behavior of Users of Online Game Mobile Legend: Bang-Bang". The purpose of this study was to find out how students' communication behavior changes after using the online game Mobile Legend: Bang-Bang and to find out how the activities of students after using the online game Mobile Legend: Bang-Bang. The theory related to this research is the uses and effects theory. This study uses a qualitative research methodology with a case study approach. The results of this study are changes in students' communication behavior towards people around them depending on their mood when they play the game. If they lose in the game, they will feel annoyed and angry which will carry over to the people around them, but when they win, they will feel happy and carry out activities as usual. Then there are no negative behaviors such as fighting that students follow from the game; students only tend to be carried away by harsh words in the game. Although the game has nothing to do with special subjects in the students' schools, there is knowledge that they get, namely knowing and understanding new foreign language vocabulary that can be practiced in the real world.